Relaç\~ao bilateral com vocaç\~ao regional: Integraç\~ao de infraestrutura, produtiva e comercial entre Brasil e Chile - Julia de Souza Borba Gonçalves; Helitton Christoffer Carneiro; Pedro Silva Barros (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– Today, the relationship between Brazil and Chile can be characterized by three aspects: i) Brazil and Chile have a bilateral relationship with a regional vocation; ii) Brazil has an integral presence in Chile; and iii) a progressive reduction in distances and an increase in connections (physical and digital infrastructure) between them. This study presents the overview of bilateral relations between Brazil and Chile and the infrastructure integration projects between the two countries. It analyzes trade, investment, transportation, logistics, energy, natural resources, and lithium, and proposes an agenda for the Brazil-Chile relations.
Keywords: F15; L95; N78; 330; bilateral relations; Brazil; Chile; regional integration; bioceanic corridor; energy transition; trade and gender